Conductive corrosion-resistant hydrophobic PVD (Physical Vapor Deposition) coating as well as preparation method and application thereof
By designing geometric patterns on the surface of the substrate and depositing TIN, Tinbn, and Tinbcn coating, the problem of both fuel cell dual -board conductivity, corrosion resistance and hydrophobic performance, and achieve high -performance coating.
Patent Information
- Application Number
- CN202411477441.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The prior art is difficult to achieve both conductivity, corrosion resistance and hydrophobic properties on fuel cell bipolar plates.
By designing geometric patterns on the surface of the substrate and sequentially depositing TiN, TiNbN and TiNbCN coatings, the conductivity, corrosion resistance and hydrophobic properties of the coating are improved.
It achieves a balance between the electrical conductivity, corrosion resistance and hydrophobicity of the coating, and improves the performance and reliability of the fuel cell bipolar plate.
Smart Images

Figure BDA0005096487020000071 
Figure BDA0005096487020000081 
Figure BDA0005096487020000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a conductive, corrosion-resistant and hydrophobic PVD coating and a preparation method and application thereof. Background Art
[0002] Green energy is favored by all countries, and green fuel cells are particularly prominent. Fuel cell bipolar plates are the core components of fuel cells, which directly affect the manufacturing cost, service safety and reliability of fuel cells. Metal bipolar plates are required to be conductive, corrosion-resistant, wear-resistant and hydrophobic, so the surface protective coating of fuel cell bipolar plates has become a research hotspot. Some studies on surface protective coatings are also disclosed in the prior art. For example, patent CN114525471A discloses the use of arc ion plating technology to deposit a Cr-based coating on a stainless steel surface; patent CN114457311A discloses the use of magnetron sputtering technology to deposit a TiZrHfMoW high entropy alloy coating on a titanium metal surface; patent CN112111716A discloses the use of radio frequency magnetron sputtering technology to deposit a Ti-TiN-amorphous carbon coating on a metal substrate surface; patent CN114277344A discloses the use of magnetron sputtering technology to deposit Ti, aC:H:Ti intermediate layer and graphite-like layer on the surface of a titanium plate; patent CN112993300A discloses the use of arc ion plating technology to deposit an oxide coating on the surface of a 316L stainless steel substrate.
[0003] Conductivity, corrosion resistance, wear resistance and hydrophobicity are the key factors affecting the commercial application of physical vapor deposition coatings. However, existing coatings usually cannot take into account the above three properties. For example, patents CN114525471A and CN114457311A take conductivity into consideration, but the metal layer has poor resistance to high-temperature molten salt corrosion; CN112111716A and CN114277344A take corrosion into consideration, but reduce the conductivity of the coating. Patent CN106756784A found that NbN coating has good conductivity, so TiN and NbN are compounded to obtain a film with good conductivity and corrosion resistance, but the hydrophobicity of the film is not considered.
[0004] Therefore, how to design a coating that takes into account electrical conductivity, corrosion resistance and hydrophobicity at the same time has become a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a conductive, corrosion-resistant and hydrophobic PVD coating and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a conductive, corrosion-resistant and hydrophobic PVD coating, comprising a TiN layer, a TiNbN layer and a TiNbCN layer sequentially deposited on the surface of a substrate;
[0008] The surface of the substrate has a geometric pattern.
[0009] Preferably, the shape of the geometric pattern includes pits; the diameter of the pits is 10 to 100 μm, the depth of the pits is 1 to 50 μm, and the distance between two adjacent pits is 20 to 200 μm.
[0010] Preferably, the thickness of the TiN layer is 0.05-0.5 μm, the thickness of the TiNbN layer is 0.5-6 μm, and the thickness of the TiNbCN layer is 0.2-3 μm.
[0011] Preferably, the material of the substrate includes one of stainless steel, titanium alloy and aluminum alloy.
[0012] The present invention provides a method for preparing the conductive, corrosion-resistant and hydrophobic PVD coating described in the above technical solution, comprising the following steps:
[0013] (1) machining a geometric pattern on the surface of a substrate, degreasing, drying, and AEGD ion etching cleaning to obtain a substrate with a geometric pattern;
[0014] (2) A TiN layer, a TiNbN layer and a TiNbCN layer are sequentially deposited on the surface of the substrate processed with the geometric pattern obtained in step (1) to obtain the conductive, corrosion-resistant and hydrophobic PVD coating.
[0015] Preferably, in step (1), the AEGD ion etching cleaning comprises the following steps: evacuating to 10 -3 Pa, then turn on the ion source and the target power supply, and apply a negative bias electric field on the substrate surface to make the argon ions perform ion etching on the substrate surface; the current of the ion source is 40-100A, the current of the target is 80-160A, and the negative bias voltage applied to the substrate surface during the etching process is -200V, -400V, -600V, -800V, -600V and -400V, respectively, and the corresponding etching times are 2min, 5min, 10min, 6min, 5min and 2min, respectively, and the temperature of the substrate is 400-550°C.
[0016] Preferably, in step (2), the deposition parameters of the TiN layer include: nitrogen flow rate of 300-700 sccm, target material of titanium, target current of 120-200 A, substrate bias of -40 V to -120 V, deposition time of 5 to 50 min, and deposition temperature of 400 to 550 °C.
[0017] Preferably, in step (2), the deposition parameters of the TiNbN layer include: nitrogen flow rate of 400-800sccm, target material of TiNb, target current of 120-200A, substrate bias of -60V--120V, deposition time of 10-120min, and deposition temperature of 400-550°C.
[0018] Preferably, in step (2), the deposition parameters of the TiNbCN layer include: a nitrogen flow rate of 400 to 800 sccm, an acetylene flow rate of 5 to 20 sccm, a target material of TiNb, a target current of 120 to 200 A, a substrate bias of -60 V to -120 V, a deposition time of 5 to 60 min, and a deposition temperature of 400 to 550 ° C.
[0019] The present invention also provides the use of the conductive, corrosion-resistant and hydrophobic PVD coating described in the above technical solution in a fuel cell bipolar plate or a corrosion-resistant mold.
[0020] Compared with the prior art, the present invention has the following advantages and technical effects:
[0021] The present invention improves the contact behavior between the substrate and water by designing a geometric pattern on the substrate surface, which is beneficial to the discharge of water and improves the hydrophobicity of the coating; TiN, TiNbN and TiNbCN coatings are then deposited in sequence on the substrate surface processed with the geometric pattern, thereby improving the conductivity and corrosion resistance of the coating and further improving the hydrophobicity of the coating, thereby obtaining a PVD coating with conductivity, corrosion resistance and hydrophobicity. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0024] The embodiment of the present invention provides a conductive, corrosion-resistant and hydrophobic PVD coating, comprising a TiN layer, a TiNbN layer and a TiNbCN layer sequentially deposited on the surface of a substrate;
[0025] The surface of the substrate has a geometric pattern.
[0026] The present invention improves the contact behavior between the substrate and water by designing a geometric pattern on the substrate surface, which is beneficial to the discharge of water and improves the hydrophobicity of the coating; TiN, TiNbN and TiNbCN coatings are then deposited in sequence on the substrate surface processed with the geometric pattern, thereby improving the conductivity and corrosion resistance of the coating and further improving the hydrophobicity of the coating, thereby obtaining a PVD coating with conductivity, corrosion resistance and hydrophobicity.
[0027] In a preferred embodiment, the shape of the geometric pattern includes pits; the diameter of the pits is 10-100 μm, the depth of the pits is 1-50 μm, and the distance between two adjacent pits is 20-200 μm.
[0028] In a preferred embodiment, the thickness of the TiN layer is 0.05-0.5 μm, the thickness of the TiNbN layer is 0.5-6 μm, and the thickness of the TiNbCN layer is 0.2-3 μm. The TiN layer in the present invention plays the role of a base layer, and is arranged near the substrate layer to improve the bonding force between the coating and the substrate; the TiNbN layer plays the role of an intermediate layer, which is used to adjust the interface and stress distribution, improve the bonding force and corrosion resistance of the coating, and has excellent electrical conductivity, so it is used as an intermediate layer; the TiNbCN layer plays the role of a functional layer, and is used as the outermost layer, which has the advantages of electrical conductivity, corrosion resistance and wear resistance.
[0029] In a preferred embodiment, the material of the substrate includes one of stainless steel, titanium alloy and aluminum alloy.
[0030] The present invention provides a method for preparing the conductive, corrosion-resistant and hydrophobic PVD coating described in the above technical solution, comprising the following steps:
[0031] (1) machining a geometric pattern on the surface of a substrate, degreasing, drying, and AEGD ion etching cleaning to obtain a substrate with a geometric pattern;
[0032] (2) A TiN layer, a TiNbN layer and a TiNbCN layer are sequentially deposited on the surface of the substrate processed with the geometric pattern obtained in step (1) to obtain the conductive, corrosion-resistant and hydrophobic PVD coating.
[0033] The present invention first processes a geometric pattern on the surface of a substrate and performs AEGD ion etching and cleaning, and then sequentially deposits a TiN layer, a TiNbN layer and a TiNbCN layer on the surface of the substrate, thereby obtaining a PVD coating with a geometric pattern on the surface. The obtained PVD coating has the multifunctional properties of being conductive, corrosion-resistant and hydrophobic.
[0034] In a preferred embodiment, in step (1), the method of machining a geometric pattern on the surface of the substrate comprises laser beam machining, ion beam machining or electric spark machining.
[0035] In a preferred embodiment, in step (1), the AEGD ion etching cleaning comprises the following steps: evacuating to 10 -3 After 1000 Pa, argon gas is introduced, and then the ion source and target power supply are turned on, and a negative bias electric field is applied to the substrate surface, so that the argon ions perform ion etching on the substrate surface; the current of the ion source is 40-100A, the current of the target is 80-160A, and the negative bias voltage applied to the substrate surface during the etching process is -200V, -400V, -600V, -800V, -600V and -400V, respectively, and the corresponding etching time is 2min, 5min, 10min, 6min, 5min and 2min, respectively, and the temperature of the substrate is 400-550°C. The present invention removes pollutants on the substrate surface by AEGD ion etching cleaning; the process parameters of AEGD ion etching cleaning are controlled within the above range, and it has the advantage of high film-substrate bonding.
[0036] In a preferred embodiment, in step (2), the deposition parameters of the TiN layer include: nitrogen flow rate of 300-700sccm, target material of titanium, target current of 120-200A, substrate bias of -40V--120V, deposition time of 5-50min, and deposition temperature of 400-550°C. The present invention deposits the TiN layer under the above conditions, regulates the bonding force between the coating and the substrate, and has good conductivity and corrosion resistance. Changing the deposition parameters of the TiN layer will change the coating thickness and density, thereby affecting the coating bonding force and conductivity.
[0037] In a preferred embodiment, in step (2), the deposition parameters of the TiNbN layer include: nitrogen flow rate of 400-800sccm, target material of TiNb, target current of 120-200A, substrate bias of -60V--120V, deposition time of 10-120min, and deposition temperature of 400-550°C. The present invention has the advantages of conductivity, adjustment of interface hardness and stress, and corrosion resistance by depositing the TiNbN layer under the above conditions. Changing the deposition parameters of the TiNbN layer will change the organizational structure, grain size, hardness, compactness, corrosion resistance, and conductivity of the coating.
[0038] In a preferred embodiment, in step (2), the deposition parameters of the TiNbCN layer include: nitrogen flow rate of 400-800sccm, acetylene flow rate of 5-20sccm, target material of TiNb, target current of 120-200A, substrate bias of -60V--120V, deposition time of 5-60min, and deposition temperature of 400-550°C. The present invention has the advantages of conductivity and corrosion resistance by depositing the TiNbCN layer under the above conditions. Changing the deposition parameters of the TiNbCN layer will affect the conductivity and corrosion resistance of the coating.
[0039] The present invention also provides the use of the conductive, corrosion-resistant and hydrophobic PVD coating described in the above technical solution in a fuel cell bipolar plate or a corrosion-resistant mold.
[0040] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0041] Example 1
[0042] A method for preparing a conductive, corrosion-resistant and hydrophobic PVD coating, the specific process is as follows:
[0043] (1) Polish the 316L stainless steel substrate to a surface roughness of <0.1 μm;
[0044] (2) Using a femtosecond laser, a pit pattern was processed on the surface of a 316L stainless steel substrate. The pit diameter was 50 μm, the depth was 5 μm, and the distance between two adjacent pits was 50 μm.
[0045] (3) The 316L stainless steel substrate with the pit pattern processed on the surface in step (2) is degreased and blown dry, and then placed in an arc ion plating furnace, and the furnace is evacuated to 10 -3 Pa, and heat the 316L stainless steel substrate to 420°C, turn on the ion source and Ti target power supply, and apply a negative bias electric field to the surface of the 316L stainless steel substrate at the same time, so that argon ions perform AEGD etching on the surface of the 316L stainless steel substrate; wherein, the ion source current is 60A, the target current is 120A, and the negative bias voltages applied to the surface of the 316L stainless steel substrate during the etching process are -200V, -400V, -600V, -800V, -600V and -400V, respectively, and the corresponding etching times are 2min, 5min, 10min, 6min, 5min and 2min, respectively.
[0046] (4) After AEGD etching is completed, the Ti target is opened, nitrogen is introduced, and deposition is performed on the surface of the 316L stainless steel substrate to form a TiN layer with a thickness of 0.15 μm; wherein, the Ti target current is 120 A, the nitrogen flow rate is 500 sccm, the substrate bias is -60 V, the deposition temperature is 420 °C, and the deposition time is 30 min.
[0047] (5) Using TiNb as a target, nitrogen gas is introduced to deposit a TiNbN layer on the surface of the TiN layer to form a TiNbN layer with a thickness of 1.5 μm; wherein the nitrogen flow rate is 500 sccm, the target current is 160 A, the substrate bias is -80 V, the deposition time is 90 min, and the deposition temperature is 420 °C.
[0048] (6) Using a TiNb metal target, nitrogen and acetylene are introduced to deposit a TiNbCN layer on the surface of the TiNbN layer to form a TiNbCN layer with a thickness of 1 μm, thereby obtaining a TiN-TiNbN-TiNbCN coating, which is a conductive, corrosion-resistant and hydrophobic PVD coating; wherein the nitrogen flow rate is 500 sccm, the acetylene flow rate is 8 sccm, the target current is 160 A, the substrate bias is -80 V, the deposition time is 60 min, and the deposition temperature is 420 °C.
[0049] Embodiments 2 to 6
[0050] Step (1) is the same as step (1) in Example 1;
[0051] The parameters in steps (2) to (6) that are different from those in Example 1 are shown in Tables 1 to 3, and the other operation and process parameters are the same as those in Example 1.
[0052] Table 1 Parameters of the pits in Examples 2 to 6 and deposition parameters for preparing the TiN layer
[0053]
[0054]
[0055] Table 2 Deposition parameters for preparing TiNbN layers in Examples 2 to 6
[0056]
[0057] Table 3 Process parameters for preparing TiNbCN layer in Examples 2 to 6
[0058]
[0059] Performance Test:
[0060] Contact resistance: Use a contact resistance meter to test the contact resistance of the coating, apply a load of 1.0MPa, and hold the pressure for 60s.
[0061] Corrosion potential test: Shanghai Brilliance electrochemical workstation was used to test the self-corrosion potential of the coating samples. The self-corrosion potential of the coating was tested at 80°C, 0.5mol / L H2SO4+5ppm HF solution, and in a natural environment.
[0062] Contact angle test: Use a contact angle tester to measure the contact angle between water and the coating at room temperature.
[0063] The self-corrosion potential results of the conductive, corrosion-resistant and hydrophobic PVD coatings prepared in Examples 1 to 6 are shown in Table 1.
[0064] Table 4 Self-corrosion potential of conductive, corrosion-resistant and hydrophobic PVD coatings prepared in Examples 1 to 6
[0065]
[0066]
[0067] It can be seen from Table 4 that compared with the 316L stainless steel substrate, the corrosion potential and contact angle of the conductive, corrosion-resistant and hydrophobic PVD coatings prepared in Examples 1 to 6 of the present invention are significantly improved, while the contact resistance is significantly reduced, indicating that the present invention significantly improves the conductivity, corrosion resistance and hydrophobic properties of the substrate by preparing the conductive, corrosion-resistant and hydrophobic PVD coating on the surface of the substrate.
[0068] Comparative Example 1
[0069] A method for preparing a 316L stainless steel substrate with a pit pattern on the surface, the specific process is as follows:
[0070] (1) Polish the 316L stainless steel substrate to a surface roughness of <0.1 μm;
[0071] (2) A femtosecond laser was used to process a pit pattern on the surface of a 316L stainless steel substrate. The pit diameter was 50 μm, the depth was 5 μm, and the distance between two adjacent pits was 50 μm.
[0072] Comparative Example 2
[0073] A method for preparing a TiN coating, the specific process is as follows:
[0074] (1) Polish the 316L stainless steel substrate to a surface roughness of <0.1 μm;
[0075] (2) Using a femtosecond laser, a pit pattern was processed on the surface of a 316L stainless steel substrate. The pit diameter was 50 μm, the depth was 5 μm, and the distance between two adjacent pits was 50 μm.
[0076] (3) The 316L stainless steel substrate with the pit pattern processed on the surface in step (2) is placed in an arc ion plating furnace, and the furnace is evacuated to 10 -3 Pa, and then nitrogen was introduced, and titanium was used as the metal target to deposit on the surface of the 316L stainless steel substrate to form a TiN layer with a thickness of 0.15 μm; wherein, the Ti target current was 160 A, the nitrogen flow rate was 500 sccm, the substrate bias was -60 V, the deposition temperature was 420 ° C, and the deposition time was 30 min.
[0077] Comparative Example 3
[0078] A method for preparing a TiNbN coating, the specific process is as follows:
[0079] (1) Polish the 316L stainless steel substrate to a surface roughness of <0.1 μm;
[0080] (2) Using a femtosecond laser, a pit pattern was processed on the surface of a 316L stainless steel substrate. The pit diameter was 50 μm, the depth was 5 μm, and the distance between two adjacent pits was 50 μm.
[0081] (3) The 316L stainless steel substrate with the pit pattern processed on the surface in step (2) is placed in an arc ion plating furnace, and the furnace is evacuated to 10 -3 Pa, and then nitrogen was introduced, and TiNb was used as the metal target to deposit on the surface of the 316L stainless steel substrate to form a TiNbN layer with a thickness of 1.5 μm; wherein, the nitrogen flow rate was 500 sccm, the target current was 160 A, the substrate bias was -80 V, the deposition time was 90 min, and the deposition temperature was 420 °C.
[0082] Comparative Example 4
[0083] A method for preparing a TiNbCN coating, the specific process is as follows:
[0084] (1) Polish the 316L stainless steel substrate to a surface roughness of <0.1 μm;
[0085] (2) Using a femtosecond laser, a pit pattern was processed on the surface of a 316L stainless steel substrate. The pit diameter was 50 μm, the depth was 5 μm, and the distance between two adjacent pits was 50 μm.
[0086] (3) The 316L stainless steel substrate with the pit pattern processed on the surface in step (2) is placed in an arc ion plating furnace, and the furnace is evacuated to 10 -3 Pa, and then nitrogen and acetylene are introduced, and TiNb is used as the metal target to deposit on the surface of the 316L stainless steel substrate to form a TiNbCN layer with a thickness of 1 μm; wherein, the nitrogen flow rate is 500 sccm, the acetylene flow rate is 8 sccm, the target current is 160 A, the substrate bias is -80 V, the deposition time is 60 min, and the deposition temperature is 420 ° C.
[0087] Comparative Example 5
[0088] A method for preparing a TiNbN-TiNbCN coating, the specific process is as follows:
[0089] (1) Polish the 316L stainless steel substrate to a surface roughness of <0.1 μm;
[0090] (2) Using a femtosecond laser, a pit pattern was processed on the surface of a 316L stainless steel substrate. The pit diameter was 50 μm, the depth was 5 μm, and the distance between two adjacent pits was 50 μm.
[0091] (3) The 316L stainless steel substrate with the pit pattern processed on the surface in step (2) is placed in an arc ion plating furnace, and the furnace is evacuated to 10 -3 Pa, and then nitrogen was introduced, and TiNb was used as the metal target to deposit on the surface of the 316L stainless steel substrate to form a TiNbN layer with a thickness of 1.5 μm; wherein, the nitrogen flow rate was 500 sccm, the target current was 160 A, the substrate bias was -80 V, the deposition time was 90 min, and the deposition temperature was 420 °C.
[0092] (4) Using a TiNb metal target, nitrogen and acetylene are introduced to deposit a TiNbCN layer on the surface of the TiNbN layer to form a TiNbCN layer with a thickness of 1 μm; wherein the nitrogen flow rate is 500 sccm, the acetylene flow rate is 8 sccm, the target current is 160 A, the substrate bias is -80 V, the deposition time is 60 min, and the deposition temperature is 420°C.
[0093] Comparative Example 6
[0094] The difference from Example 1 is that step (2) is omitted, and the other steps are the same as Example 1.
[0095] Comparative Example 7
[0096] A NbN coating without a pit pattern, the specific process is as follows:
[0097] (1) Polish the 316L stainless steel substrate to a surface roughness of <0.1 μm;
[0098] (2) Place the polished 316L stainless steel substrate in step (1) in an arc ion plating furnace and evacuate the furnace to 10 -3 Pa, and then nitrogen was introduced, and Nb was used as the metal target to deposit on the surface of the 316L stainless steel substrate to form a NbN layer with a thickness of 3.0 μm; wherein, the Nb target current was 160 A, the nitrogen flow rate was 500 sccm, the substrate bias was -60 V, the deposition temperature was 450 ° C, and the deposition time was 60 min.
[0099] Comparative Example 8
[0100] The difference from Example 1 is that the order of step (5) and step (6) is swapped, and the rest is the same as Example 1 to obtain a TiN-TiNbCN-TiNbN coating.
[0101] Comparative Example 9
[0102] The difference from Example 1 is that the order of step (4) and step (6) is swapped, and the rest is the same as Example 1 to obtain a TiNbCN-TiNbN-TiN coating.
[0103] Comparative Example 10
[0104] The difference from Example 1 is that the order of step (4) and step (5) is swapped, and the rest is the same as Example 1 to obtain a TiNbN-TiN-TiNbCN coating.
[0105] The corrosion potential, contact angle and contact resistance of the coatings prepared in Comparative Examples 1 to 10 were tested according to the aforementioned method. The test results are shown in Table 5.
[0106] Table 5 Self-corrosion potential of coatings prepared in Example 1 and Comparative Examples 1 to 10
[0107] Corrosion potential / V Contact angle / ° <![CDATA[Contact resistance / mΩ / cm 2 > Example 1 0.18 89.7 36.4 Comparative Example 1 -0.58 45.8 120.6 Comparative Example 2 -0.36 85.1 65.7 Comparative Example 3 -0.24 85.2 41.7 Comparative Example 4 -0.16 85.4 53.8 Comparative Example 5 -0.14 85.1 52.6 Comparative Example 6 0.17 46.9 56.6 Comparative Example 7 -0.31 44.8 53.5 Comparative Example 8 -0.12 85.0 52.7 Comparative Example 9 -0.19 66.3 53.6 Comparative Example 10 -0.11 85.6 53.6
[0108] From Table 4 and Table 5, it can be seen that the corrosion potential, contact angle and contact resistance of the coatings prepared in Examples 1-6 of the present invention are: 0.01-0.18V, 84-90° and 36-54mΩ / cm 2 The larger the corrosion potential value, the better the corrosion resistance; the larger the contact angle, the better the hydrophobicity; the larger the contact resistance, the worse the conductivity of the coating. It can be seen that Example 1 has the best comprehensive performance; while Comparative Examples 1 to 10 are difficult to simultaneously obtain high corrosion potential, high contact angle and low contact resistance.
[0109] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A conductive, corrosion-resistant and hydrophobic PVD coating, characterized in that: It includes a TiN layer, a TiNbN layer and a TiNbCN layer sequentially deposited on the surface of a substrate; The surface of the substrate has a geometric pattern.
2. The conductive, corrosion-resistant and hydrophobic PVD coating according to claim 1, characterized in that: The shape of the geometric pattern includes pits; the diameter of the pits is 10 to 100 μm, the depth of the pits is 1 to 50 μm, and the distance between two adjacent pits is 20 to 200 μm.
3. The conductive, corrosion-resistant and hydrophobic PVD coating according to claim 1, characterized in that: The thickness of the TiN layer is 0.05-0.5 μm, the thickness of the TiNbN layer is 0.5-6 μm, and the thickness of the TiNbCN layer is 0.2-3 μm.
4. The conductive, corrosion-resistant and hydrophobic PVD coating according to claim 1, characterized in that: The material of the substrate includes one of stainless steel, titanium alloy and aluminum alloy.
5. The method for preparing the conductive, corrosion-resistant and hydrophobic PVD coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) machining a geometric pattern on the surface of a substrate, degreasing, drying, and AEGD ion etching cleaning to obtain a substrate with a geometric pattern; (2) A TiN layer, a TiNbN layer and a TiNbCN layer are sequentially deposited on the surface of the substrate processed with the geometric pattern obtained in step (1) to obtain the conductive, corrosion-resistant and hydrophobic PVD coating.
6. The method for preparing the conductive, corrosion-resistant and hydrophobic PVD coating according to claim 5, characterized in that: In step (1), the AEGD ion etching cleaning comprises the following steps: evacuating to 10 -3 Pa, then turn on the ion source and the target power supply, and apply a negative bias electric field on the substrate surface to make the argon ions perform ion etching on the substrate surface; the current of the ion source is 40-100A, the current of the target is 80-160A, and the negative bias voltage applied to the substrate surface during the etching process is -200V, -400V, -600V, -800V, -600V and -400V, respectively, and the corresponding etching times are 2min, 5min, 10min, 6min, 5min and 2min, respectively, and the temperature of the substrate is 400-550°C.
7. The method for preparing the conductive, corrosion-resistant and hydrophobic PVD coating according to claim 5, characterized in that: In step (2), the deposition parameters of the TiN layer include: nitrogen flow rate of 300-700 sccm, target material of titanium, target current of 120-200 A, substrate bias of -40 V to -120 V, deposition time of 5 to 50 min, and deposition temperature of 400 to 550 °C.
8. The method for preparing the conductive, corrosion-resistant and hydrophobic PVD coating according to claim 5, characterized in that: In step (2), the deposition parameters of the TiNbN layer include: nitrogen flow rate of 400-800sccm, target material of TiNb, target current of 120-200A, substrate bias of -60V--120V, deposition time of 10-120min, and deposition temperature of 400-550°C.
9. The method for preparing the conductive, corrosion-resistant and hydrophobic PVD coating according to claim 5, characterized in that: In step (2), the deposition parameters of the TiNbCN layer include: a nitrogen flow rate of 400 to 800 sccm, an acetylene flow rate of 5 to 20 sccm, a target material of TiNb, a target current of 120 to 200 A, a substrate bias of -60 V to -120 V, a deposition time of 5 to 60 min, and a deposition temperature of 400 to 550 ° C.
10. Use of the conductive, corrosion-resistant and hydrophobic PVD coating according to any one of claims 1 to 4 in a fuel cell bipolar plate or a corrosion-resistant mold.
Citation Information
Patent Citations
Nb / Nb multilayer anti-corrosion electroconductive film and preparation method thereof
CN106756784A
Preparation process of ultralow-resistance corrosion-resistant coatings for metal bipolar plates of hydrogen fuel cells
CN112111716A
Preparation method of titanium-based fuel cell bipolar plate coating
CN114277344A
High-entropy alloy nanocrystalline coating for bipolar plate of proton exchange membrane fuel cell and preparation method of high-entropy alloy nanocrystalline coating
CN114457311A
Preparation method of high-quality Cr-based coating of stainless steel bipolar plate of proton exchange membrane fuel cell
CN114525471A
Cited By
Conductive corrosion-resistant NiCrAlY / Al2O3 / TiNbN composite coating on stainless steel surface and preparation method thereof
CN120485687A